KEDUDUKAN KRISTUS DALAM PENCIPTAAN MENURUT KOLOSE 1:15-20 (TANGGAPAN KRISTOLOGI SAKSI YEHUWA) - Dicky Dominggus (Religi: Jurnal Studi Agama-agama, 2020)
In Christianity, Christology is one of the doctrines that has resulted in debate up to now. Jehovah's Witnesses are one group that does not recognize that Jesus is Lord. Their understanding is based on many texts, one of which is Colossians 1: 15-20. In Colossians 1: 15-20, Jehovah's Witnesses see Christ as the first creation. They translate the eldest word in chronological order. Based on research on the text of Colossians 1: 15-20, the firstfruits meant by Paul are more directed to the order in authority. For this reason, the view of Jehovah's Witnesses about Christ in Colossians 1: 15-20 is different from the mainstream.